Analysis of three treatment methods for granulomatous lobular mastitis: a retrospective study in a single center - Shang, Boyu; Zhang, Tianyi; Liu, Chang; Lu, Jiaxin; Cui, Can; Feng, Jing; Zhou, Yi (Frontiers in Oncology, 2025)
BackgroundGranulomatous lobular mastitis (GLM) is a rare, benign inflammatory condition of the breast that is difficult to distinguish from breast cancer on the basis of clinical and imaging findings. GLM typically has a long disease course, and is difficult to treat and prone to recurrence. Furthermore, there is currently no standard treatment for GLM. The aim of this study was to compare the therapeutic effects and patient satisfaction scores of surgery, triple anti-tuberculosis drug therapy, and combination treatment against GLM.MethodsThe medical records and follow-up data of GLM patients who underwent treatment at our center were retrospectively analyzed. Patients were divided into the treatment groups of surgery (group A), triple anti-tuberculosis drug therapy (group B), and combination therapy (group C). The demographic and clinical data, treatment outcomes, and patient satisfaction scores were compared among the three groups.ResultsMedian follow-up duration of the patients was 35.43 months (range, 13.27–67.90 months). There were 106, 109, and 88 patients in groups A, B, and C respectively. The cure rates were similar among the groups (P = 0.220), although treatment duration was longest for group B, followed by group C and group A (P < 0.001). Group B had the highest patient satisfaction scores (P < 0.001),whereas the recurrence rate was highest in Group A (P < 0.001). Furthermore, no severe adverse drug reactions or major postoperative complications were observed in any of the patients.ConclusionsTriple anti-tuberculosis drug therapy can effectively treat GLM patients with high patient satisfaction scores for potential application in clinical practice. The combination of surgery and triple anti-tuberculosis drug therapy is a suitable option for patients seeking rapid relief.Trial registrationThe study was registered at the Us Clinical Trial Registration Center (registration number: NCT06565845;date: 08/21/2024).